"A year-long, fortnightly, observational survey in three European countries of patients with respiratory allergies induced by house dust mites: Methodology, demographics and clinical characteristics". Issue 1 (December 2016) - Demoly, Pascal; Matucci, Andrea; Rossi, Oliviero; Vidal, Carmen
Abstract Background House dust mite (HDM) allergens constitute the leading trigger for the symptoms of persistent respiratory allergies (such as allergic rhinitis and asthma). However, the fluctuating, pernicious nature of the symptoms has given rise to a perception that HDM-induced respiratory allergy is not a "real" disease. Methods In order to assess the self-reported disease profile and behaviour of adult patients with a self-reported history of severe, poorly controlled, physician-diagnosed HDM respiratory allergy, we performed an observational, international, multicentre survey in three European countries (France, Italy and Spain). Participants were included in the survey if they passed a short Internet-based screening questionnaire. Following completion of a detailed post-inclusion questionnaire, 28 fortnightly telephone interviews were used to gather extensive data on the participants' symptom prevalence and intensity, medical consultations, disease burden, quality of life, and medication use from late May 2012 to early July 2013. Results Twenty-two thousand nine hundred ninety five individuals completed the Internet screening questionnaire and 339 respondents (67 % female) met all the inclusion criteria. 313 of the 339 (92 %) completed the post-inclusion questionnaire (n  = 114 in Italy, 92 in France and 107 in Spain). The median time since the first symptoms of HDM allergy was over 13 years in all three countries. The response rate for the fortnightly interviews averaged 75 % (range: 29 to 97 %). The reported fortnightly prevalence of nasal and ocular symptoms peaked in the autumn (September to November) and spring (March to May). These peaks in prevalence coincided with increased reports of symptom worsening and higher physician consultation rates. In participants not allergic to pollen, the autumn and spring peaks were accompanied by a third peak in late December 2012. Very few participants reported that their symptoms had never improved (4 %) or never worsened (11 %) during the survey period. Conclusions In a survey in France, Italy and Spain, patients with severe HDM-induced respiratory allergies experienced a complex set of changing, troublesome symptoms throughout the year, with peaks in spring, autumn and (to a lesser extent) mid-winter.